Kode vicious bugs out. - Neville-Neil, George (New York ACM, 2006)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: General Literature; General; Software; Programming techniques; Miscellaneous; Software engineering; Software/program verification; Testing and debugging